Design, synthesis and inhibitory activity against human dihydroorotate dehydrogenase (hDHODH) of 1, 3-benzoazole derivatives bearing amide units. Issue 13 (1st July 2016) - Li, Jiling; Wu, Dang; Xu, Xiaoyong; huang, Jin; Shao, Xusheng; Li, Zhong
Graphical abstract: Abstract: A series of 1, 3-benzoazole derivatives possessing amide moieties were designed, synthesized and evaluated as inhibitors against human dihydroorotate dehydrogenase ( h DHODH). CompoundsA11, A14 andA26 exhibited good to excellent activities against h DHODH at the concentration of 10 μM. In particular, compoundA14 displayed an IC50 value of 0.178 μM with 2-fold preference overA771726 . The result implied that a proper degree of steric size and electron density of the C-6 amide moiety was necessary to retain the inhibitory activity of the synthesized compounds.